The Assimilation of Assistive Technology in Residential Care Centers for People with Intellectual Disabilities - Eli Carmeli; Carmit Cahana; Joav Merrick (The Scientific World Journal)
People with intellectual disability (ID) require special support in order to achieve independence in their daily life. Persons with ID are less exposed to assistive technology, although studies have shown that the availability of aids afford an opportunity to reach independence and cooperation. The aim of this study was to examine the nature of the relationship between involvement of the physiotherapy (PT) team and the degree to which assistive technology was used. A questionnaire was sent to all PTs employed at all 54 residential care centers for persons with ID of the Division for Mental Retardation at the Ministry of Social Affairs in Israel. A significantly positive correlation was found between the degree of involvement of the PT and the utilization of assistive technology. The study results may be summarized by stating that PTs demonstrated a great deal of involvement, particularly in relation to the extent of their work in the residential care centers. PT's awareness of the importance was indicated as the major reason to use assistive technology.